Morphology and distribution of the acorn barnacle Tetraclita reni nom. nov. (Crustacea: Cirripedia) in Madagascar and adjacent waters - Chan, Benny Kwok Kan; Hsu, Chih-Hsiung; Tsai, Pei-Chen (Zootaxa, 2009)
In Madagascan waters, both Tetraclita rufotincta Pilsbry 1916 and T. africana Ren 1989 have been reported. Tetraclita rufotincta is more widely distributed than T. africana, extending to the western Indian Ocean and east Africa. Tetraclita africana is reported from Madagascar and no further distribution record has been made apart from its type locality. Both species have pink parietes and are similar in size, which could lead to identification confusion. In this study, we revealed that T. africana differed from T. rufotincta in having multicuspidate setae on cirrus III, a feature that can be observed with both light microscopy and SEM. Additionally, the tergum of T. africana has a rounded spur and a larger basi-scutal angle than that of T. rufotincta. However, since the name Tetraclita africana has been pre-occupied under the name Tesseropora (Tetraclita) wireni africana Nilsson-Cantell, 1932, we, therefore, propose herein a replacement name, Tetraclita reni nom. nov. Based on museum specimens examined, Tetraclita reni nom. nov. is present in northeastern and southern Madagascar and Mauritius but absent from Yemen, Kenya, South Africa, Aldabra and northwestern Madagascar, suggesting the distribution of T. reni nom. nov. could be confined to the south and northeast of Madagascar and adjacent waters.